2004
DOI: 10.4049/jimmunol.172.4.2256
|View full text |Cite
|
Sign up to set email alerts
|

Human Cytomegalovirus Proteins pp65 and Immediate Early Protein 1 Are Common Targets for CD8+ T Cell Responses in Children with Congenital or Postnatal Human Cytomegalovirus Infection

Abstract: Recombinant modified vaccinia Ankara- and peptide-based IFN-γ ELISPOT assays were used to detect and measure human CMV (HCMV)-specific CD8+ T cell responses to the pp65 (UL83) and immediate early protein 1 (IE1; UL123) gene products in 16 HCMV-infected infants and children. Age at study ranged from birth to 2 years. HCMV-specific CD8+ T cells were detected in 14 (88%) of 16 children at frequencies ranging from 60 to >2000 spots/million PBMC. Responses were detected as early as 1 day of age in infants wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
76
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 107 publications
(81 citation statements)
references
References 66 publications
4
76
0
Order By: Relevance
“…Within the numerous antigens recognized by memory CD8+ T cells of healthy HCMVseropositive donors tested with various HLA haplotypes, IE1 and pp65 were the most immunodominant, conWrming observations claimed by several groups for many years. Moreover, CTL detected in young infants with HCMV infection were directed at both IE1 and pp65 and their appearance correlated with decrease in viral load [21,22]. This supports the notion that immunodominance could be governed by antigenic dominance, reXecting antigen amounts available at the right time when immunoevasins are not yet eVective.…”
Section: T Cell Repertoire Against Hcmv Exhibits a Broad Pattern Of Ssupporting
confidence: 66%
“…Within the numerous antigens recognized by memory CD8+ T cells of healthy HCMVseropositive donors tested with various HLA haplotypes, IE1 and pp65 were the most immunodominant, conWrming observations claimed by several groups for many years. Moreover, CTL detected in young infants with HCMV infection were directed at both IE1 and pp65 and their appearance correlated with decrease in viral load [21,22]. This supports the notion that immunodominance could be governed by antigenic dominance, reXecting antigen amounts available at the right time when immunoevasins are not yet eVective.…”
Section: T Cell Repertoire Against Hcmv Exhibits a Broad Pattern Of Ssupporting
confidence: 66%
“…Thus, it seems that the determination of IE-and pp65-specific CD8 + T cells may in some cases underestimate the real efficiency of the immune system against HCMV infection. In this respect, it seems important to recall that changes in the protein and epitope specificity of HCMVspecific CD8 + T cells over time have been reported in children with congenital or postnatal HCMV infection [18] as well as during Epstein-Barr virus infection [19]. This might be due to different viral antigen processing and presentation [20].…”
Section: Discussionmentioning
confidence: 99%
“…Longitudinal samples were collected from young infants with ages ranging from 1 wk to 2.5 y. Prior reports from our group (63)(64)(65) and others (66) have shown that HCMV-specific CD8 + T-cell responses with similar antigen specificity, phenotype, and functional profiles as adults are detectable in infants with congenital CMV infection, even during gestation. Other studies have shown that infants can generate HIV-specific CD8 + T-cell responses that exert selective pressure and contribute to the evolution of viral quasi-species over the first year of life (67).…”
Section: Discussionmentioning
confidence: 99%